Extracorporeal Shock Wave Lithotripsy in Prone and Supine Positions for Patients with Upper Ureteral Calculi - Zomorrodi, Afshar; Elahian, Amirreza; Ghorbani, Nematollah; Tavoosi, Anahita (Urology Journal, 2009)
Introduction: The aim of this study was to evaluate the treatment of upper ureteral calculi with extracorporeal shock wave lithotripsy (SWL) in the supine and prone positions. Materials and Methods: A total of 68 patients with upper ureteral calculi underwent SWL. In 35 patients, the procedure was performed in the supine position (group 1), while in the 33 remainders, it was performed in the prone position (group 2). The stone-free rate, the number of SWL sessions required, and the number of shocks per treatment session were compared between the 2 groups. Results: The mean calculus size was 12.4 Â± 3.1 mm and 12.2 Â± 2.9Â mm in groups 1 and 2, respectively. The stone-free rate was 81.8% in group 1 and 82.9% in group 2 (P = .91). The number of sessions for achieving the stone-free status was similar in the patients of the 2 groups (1.9 Â± 0.8 in group 1 versus 1.9 Â± 0.8 in group 2; P = .79). The meanÂ number of shock waves per treatment session was not significantly different between the 2 groups. No major complications were seen and none of the patients required hospitalization, placement of a ureteral catheter, or a double-J stent. Conclusion: Our study showed that in the prone position, treatment of the upper ureteral calculi by SWL is as safe and effective as the supine position.